"I just took the beating": indigenous peoples’ experiences with police use of force - Laming, Erick (International journal of law, crime and justice, 2023)
Police use of force is a critical area of concern, in Canada, North America, and globally. Drawing on in-depth interviews with 40 Indigenous community members, this article provides insight into direct and vicarious experiences with police use of force. The research illustrates that most Indigenous respondents have experienced police use of force—either directly, vicariously, or both. Most of the experiences with police use of force involved physical types of encounters. In many cases, individuals were injured but did not receive medical attention. The findings underscore the variety of ways Indigenous peoples have experienced police use of force and how these encounters have had negative long-term impacts. Policy implications such as stronger accountability and reporting mechanisms for documenting use of force as well as the implementation of body-worn cameras for police are examined.